Evaluating the recovery of pan-susceptible and antibiotic-resistant Escherichia coli in synthetic test agricultural water using membrane filtration and colilert methods - Zirui Ray Xiong; Ajani A. Brooks; Ellen Gabriel; Alan Gutierrez; Shayla B. Johnson; Cheryl East; Lisa M. Durso; Elica Moss; Manan Sharma (BMC Research Notes)
Abstract Membrane filtration and Colilert assays are commonly used to quantify Escherichia coli levels in agricultural water. These methods have not been evaluated in test agricultural water (TAW), a formulation used for assessing chemical sanitizer effectiveness. Quantitative recovery of E. coli in TAW may be affected by turbidity levels. TAW was formulated with a pH value of 6.5 at two turbidity levels (0 and 50 NTU). Pan-susceptible and cefotaxime-resistant E. coli strains were added separately to TAW (200 CFU/100 mL). Inoculated TAW was either (1) filtered using a 0.45 μm membrane filter (MF) and placed onto Tryptone Bile X-Glucuronide (TBX) agar or CHROMagar ECC (ECC), or (2) tested by IDEXX Quanti-Tray/2000 Colilert. Recovery percentages of E. coli at both turbidity levels were similar on TBX and ECC, but pan-susceptible E. coli ARS C101 in TAW at 50 NTU on TBX was not quantifiable. For Colilert assays, the recovery percentages of E. coli from 0 NTU and 50 NTU TAW were between 93.4 ± 4.4% and 127.0 ± 10.5%. Overall, ECC and Colilert provided quantifiable results for recovery of pan-susceptible and cefotaxime-resistant E. coli from artificial agricultural water at different turbidity levels. Higher levels of turbidity affected the ability to quantify E. coli by MF with TBX and recovery by Colilert.